Characteristic in ground motions between the Mw7.9 Pazarcık earthquake and the Mw7.6 Elbistan earthquake in Türkiye - Peibin Xu; Xingguo Liu; Lin Li (Scientific Reports)
Abstract On February 6, 2023, two destructive earthquakes occurred in Türkiye, namely, the Pazarcık earthquake with moment magnitude 7.9 and the Elbistan earthquake with moment magnitude 7.6. A larger number of strong motion recordings were obtained in both events, facilitating the examination of their ground motion characteristics. Using four ground-motion prediction equations (GMPEs)—two regional and two global—we computed total residual (R es), between-events residual (δB e ), within-event residual (δW es ) and adjustment coefficient of anelastic attenuation (Δc 3), for peak ground acceleration (PGA), pseudo-spectral accelerations (PSAs) and 5–95% significant duration. Both regional and global GMPEs exhibit period- and distance-dependent for R es, which can be attributed to discrepancy in tectonic settings and geological conditions among different regional datasets used in their development, leading to variations in ground motion. Predominantly negative δB e values at periods T < 0.2 s for both earthquakes (except for positive values in the Pazarcık event for the Kale2015 model) indicate: source effects are weaker than the average levels represented by the GMPEs, and stronger than those characterized by specific-regional model Kale2015 for the Pazarcık earthquake. The observed increasing trend in δB e values at periods T > 0.6 s, which can be attributed to supershear rupture (via Mach wave amplification) and forward rupture directivity. Predominantly negative Δc 3 values (Pazarcık earthquake: −0.0002 to −0.0073; Elbistan earthquake: −0.0001 to −0.0204) indicate faster anelastic attenuation in the affected zone of both earthquakes than regional averages presented by all GMPEs, aligning with prior studies of the East Anatolian Fault. These results provided valuable insights for improving regional seismic hazard models.